Microvascular Reconstruction in the Setting of Difficult Vascular Anatomy: The Reverse Arterial Flow Technique. (23rd August 2013) - Deschler, Daniel G.; Lin, Alice
Abstract : Objectives: We present one case where challenging vascular anatomy was circumvented by changing the conventional vascular dissection and geometry successfully. Methods: Variations in the quality and suitability of donor vessel anatomy can significantly impact microvascular free tissue transfer reconstruction and may require innovative approaches to allow successful revascularization. Although greatest variability is noted in the venous system of transferred tissue segments, arterial anatomy and quality can also be severely limiting. However, unlike the recipient vessels where multiple options may be available, there is only one available donor artery. In the setting of unfavorable physical properties of the artery, the reconstructive surgeon is often forced to sacrifice the flap in favor for a second harvest. Results: In our case, the artery was affected by Monckeberg's arteriosclerosis, which is a process of arterial calcification classically described as calcification of the tunica media of the arterial wall. This creates a hardened wall through which microvascular suture cannot be passed and microvascular anastomosis is not successful. Conclusions: In our case, the fibula free flap was salvaged by using the distal end of the artery for anastamosis to create reverse flow perfusion of the flap. We present the details of the technique required for harvest and inset of a reverse arterial flow fibula free flap.